Hubungan Tingkat Pengetahuan Kanker Serviks Dengan Minat Untuk Vaksinasi HPV Pada MahasiswiI Fakultas Kedokteran Universitas HKBP Nommensen Medan - Hendra Jirwanto; Surya Dirgahayu Purba (Nommensen Journal of Medicine, 2021)
Background: Cervical cancer is an excessive abnormal cell growth around the cervix area. Cervical cancer wascaused by many factors, and Human Papillomavirus (HPV) plays an important role in the growth of cervical cancer. HPV vaccine plays a major note in reducing the incidence rate of cervical cancer. The interest of HPV vaccination was affected by the level of knowledge of cervical cancer.Objective: To show the correlation between the level of knowledge of cervical cancer and the interest in HPVvaccination in students of the Medical Faculty of HKBP Nommensen Medan.Methods: This study was an analytical study with a cross-sectional design. Samples were selected by totalsampling and the total number of the samples were 148 respondents.Results: This study shows among 148 respondents; there are 62 students (41,8%) have good level of knowledgeabout cervical cancer, 80 students (54,1%) have an average level of knowledge about cervical cancer and 6students (4,1%) have low level of knowledge about cervical cancer. Moreover for interest, among 148 respondents, there are 136 students (91,8%) show interest in HPV Vaccination.Conclusion: There is no significant correlation between level of student’s knowledge about cervical cancer andthe interest of HPV Vaccination.